ANALISIS DISTRIBUSI NANAS DI DESA WONOREJO TRISULO KECAMATAN PLOSOKLATEN KABUPATEN KEDIRI - Bimantara, Haidar; Budiraharjo, Kustopo; Roessali, Wiludjeng (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
The research objective was to analyze the distribution channel model and the factors that influence the marketing efficiency of pineapple in the Village of Wonorejo Trisulo, District Plosoklaten, Kediri Regency. The research was conducted on 10 September - 10 October 2020 located in the Wonorejo Trisulo Village, Plosoklaten District, Kediri Regency. The research method used survey. The number of respondents was 144 people. The samples were determined using the Slovin formula consisting of 86 pineapple farmers. Furthermore, the snowball sampling method was used to determine the marketing agency respondents, namely 4 collectors, 8 wholesalers, and 16 retailers. The primary data obtained from interviews with based on questionnaires that has been prepared. Secondary data were obtained from related institutions and agencies such as the Central Statistics Agency (BPS), monographs of Wonorejo Trisulo Village, literature, and other supporting sources. The data analysis used was the descriptive quantitative method and statistical analysis. The results showed that the pineapple distribution channel in Wonorejo Trisulo Village was divided into 3 channels. The most efficient channel was channel 3 characterized by the lowest created marketing margin (IDR 4,650) and the highest farmer share value (63.59%). Results revelead that the farmer price level, and marketing margin were found significant in affecting the marketing efficiency. T-test results showed that partially the price variables at the farmer level and marketing margins effects on the efficiency of pineapple marketing, while the marketing channel variables had no effect on the marketing efficiency of pineapples in the Wonorejo Trisulo Village, Plosoklaten District, Kediri Regency.